Erratum to “Development of immunohistochemistry and enzyme-linked immunosorbent assays for the detection of circulating antibodies against Enteromyxum scophthalmi (Myxozoa) in turbot (Scophthalmus maximus L.)” [Fish Shellfish Immunol. 17 (2004) 335–345] - Sitjà-Bobadilla, Ariadna; Redondo, Mª José; Macías, M. A.; Ferreiro, Isabel; Riaza, Ana; Álvarez-Pellitero, Mª del Pilar (Fish & Shellfish Immunology, 2005)
The publisher would like to apologise for an error in the reproduction of Fig. 1 in the above paper. This figure should have appeared in colour as it does on the following page. The full article, with the figure in colour, can also be accessed at http://www.sciencedirect.com. Peer reviewed